1992
DOI: 10.1243/pime_proc_1992_206_157_02
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Repeatability of Dynamic Tyre Forces Generated by Heavy Vehicles

Abstract: Road damage due to heavy vehicles is thought to be dependent on the extent to which lorries in normal tra& apply peak forces to the same locations along the road. A validated vehicle simulation is used to simulate 37 leaf-sprung articulated vehicles with parametric variations typical of vehicles in one weight class in the highway vehiclefleet. The spatial distribution of tyre forces generated by each vehicle is compared with the distribution generated by a reference vehicle, and the conditions are established … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…Nevertheless, the larger amplitude components of the true forces are predicted very well. These peaks are an important factor in relation to pavement and bridge damage as they can indicate specific locations in pavements where damage will be concentrated (Cole and Cebon 1992). Table 1 presents the Root Mean Square Error (RMSE) of the identified forces expressed as a percentage of the maximum absolute true force magnitude.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the larger amplitude components of the true forces are predicted very well. These peaks are an important factor in relation to pavement and bridge damage as they can indicate specific locations in pavements where damage will be concentrated (Cole and Cebon 1992). Table 1 presents the Root Mean Square Error (RMSE) of the identified forces expressed as a percentage of the maximum absolute true force magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that dynamic vehicle axle forces can increase the average road surface damage by up to four times compared to that caused by static axle forces alone (Cole and Cebon, 1992). Therefore, the minimisation of dynamic axle forces is important in order to promote long pavement life spans and ensure that bridge loads are small.…”
Section: Introductionmentioning
confidence: 99%
“…and s y (w i ) is the Power Spectral Density (PSD) roughness in terms of wave number, i, which represents the spatial frequency [24]: (8) where w 0 is the discontinuity wave number and n 1 and n 2 define the slopes. According to [30] the discontinuity between two branches of the PSD happens at a wavelength of approximately 6.3m, which is 1/2π cycles/metre taken as the datum value for s y (w 0 ).…”
Section: Road Surface Profilementioning
confidence: 99%
“…Cole and Cebon [8] also tried to reproduce patterns of spatial repeatability but did not allow for the variability in the vehicle dynamic properties. This paper describes a computer model which predicts the dynamic behaviour of a truck fleet.…”
Section: Introductionmentioning
confidence: 99%
“…Cole & Cebon [4] performed a numerical investigation of spatial repeatability using an experimentally validated two-dimensional articulated vehicle model. They generated a fleet of thirty-seven leaf sprung vehicle models with similar geometry and eight varying parameters relating to the ride characteristics, identifying repeatable patterns of dynamic tyre forces.…”
Section: Introductionmentioning
confidence: 99%